PENTINGNYA PELATIHAN E-COMMERCE GUNA MENINGKATKAN PENJUALAN UMKM KEGIATAN MAHASISWA INDO GLOBAL MANDIRI MENDUKUNG MBKM - Suryati; Azizah, Tyara Nur; Hertati, Lesi; Terttiaavini; Heryati, Agustina; Asmawati (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2021)
E-commerce or electronic commerce is currently growing rapidly in the era of technology that is increasingly advanced along with the times. E-commerce is one of the trading or sales media that is in great demand by the community at this time so that it can sell, buy, and promote products using online media as online buying and selling transactions. The sale of clothing products using E-commerce is very profitable for both sellers and buyers. With the increasingly sophisticated technology and gadgets, buyers no longer bother to choose the clothes they want without being tired of going around choosing clothes, even if only by using a cellphone, buyers can already buy clothes that are out of town and even abroad using E-commerce, so that sellers can market their products not only in the surrounding area.